Ground Control Points along the coastal plain of Babitonga Bay-Santa Catarina-Brazil - Marcelo Cancela Lisboa Cohen; Neuza Fontes; Érika do Socorro Ferreira Rodrigues; Luiz C R Pessenda; Marlon França; Ed Garret; Junghyung Ryu (PANGAEA, 2025)
Ground Control Points (topography) obtained along the coastal plain of Babitonga Bay- Santa Catarina, Brazil. Fieldwork was conducted in August 2017 to collect planialtimetric data using a Trimble Catalyst antenna equipped with a Differential Global Navigation Satellite System (GNSS) with a sub-meter correction. The planimetric data (±30 cm) and altimetric data (±10 cm) for the GCPs were obtained using the Catalyst and theodolite, respectively. Coordinates of Ground Control Points were obtained by drone aerophotogrammetry using the Agisoft Metashape Professional version 1.8.4.
In: Cohen, MCL et al. (2025): Topographic, vegetation, radiocarbon and stratigraphic data from Babitonga Bay-Santa Catarina-Brazil [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.985002